Motivation in teenagers to study English Language with and without technology - Marino Ramírez, Humberto (CIEX JOURNAL, 2025)
Motivation represents a very important element in teaching the English language, because a motivated student does what he’s asked for in class and at home. A certain percentage of students in each high school classroom does not show interest in learning English, therefore, the aim of this research is to analyze the most significant elements for motivating students learning English, both with and without technology. The approach used was qualitative, using a documentary research method, through a systematic literature review, this study analyzes the main forms of motivation, along with the latest technological advances in motivating through artificial intelligence, chatbots, and gamification. It was found that teachers are primarily responsible for motivating, along with parents and classmates. Technology is a powerful tool for continuing to develop the language with intrinsic motivation and student autonomy.